Fakhruddin al-Razi and Sigmund Freud's Perspectives on the Concept of the Human: A Comparative Analysis - Nur Fajriati N Khoir; Ghozali Ghozali (Tasfiyah: Jurnal Pemikiran Islam, 2023)
The discourse of the human concept is an important theme constantly being studied because humans have a natural disposition to understand and understand themselves. Fakhruddin Ar-Razi and Sigmund Freud are a few who focus on studying the concept of humans. Both are important figures in the development of science. Between ar-Razi and Freud, they had a view on it. The author at least uses a descriptive analysis method with a comparative study of each character’s opinion. This paper at least examines the differences and similarities in their views about the human concept regarding personality structure, the basis of human action and the goals of human behaviour. According to ar-Razi and Sigmund Freud, the results can be seen to what extent the similarities and differences regarding human conception. The conclusion of this research, from the point of view of Islamic worldview represented by Fakhruddin al-Razi’s thoughts, is that humans are seen comprehensively not only to have natural potential (ḥayawāniyah) but also nabatiyyah dan insaniyyah.